ВИСОКОШВИДКІСНИЙ ЗАХИСТ ДЛЯ ПАРАЛЕЛЬНОЇ ЛІНІЇ ЕЛЕКТРОПЕРЕДАЧІ З ЄМНІСНОЮ КОМПЕНСАЦІЄЮ - Пеж, П.; Росоловські, Є.; Ижиковські, Я. (Інститут електродинаміки НАН України, Київ, 2018)
This paper describes a novel idea for fast protection of parallel series-compensated transmission lines operating in various configurations. It is based on the logic diagram of flag signals, which are determined using only one-end phase currents measurements. The developed method has been tested and evaluated using signals obtained from computer simulations. The detailed models of considered transmission line including the SC&MOV banks as well as the measurement channels have been developed. Using these models, the reliable data for fault on a double-circuit series-compensated transmission line, as well as for faults outside the line, have been generated under variety of fault scenarios. The sample test-case results of algorithm operation, as well as statistical evaluation are presented and discussed. References 10, table 1, figures 5.